2012
DOI: 10.4028/www.scientific.net/amr.610-613.3394
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as a Thickener for Direct Printing of Natural Dye on Cotton Fabric

Abstract: Development of chitosan as a thickener for direct printing of natural dye on cotton fabric was investigated. Chitosan was applied as a thickener at various concentrations and its effect on the print properties was determined in comparison with the typical printing thickener, sodium alginate. The results exhibited that chitosan affected the fabric properties by increasing fabric yellowness and stiffness. However, with increasing chitosan concentrations, the yellowness reduced only marginally. Direct printing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…A wide range of chitosan exists with various molar masses from 100 000 g/mol up to 500 000 g/mol with acetylation degree between 0 and 30% . Many interesting applications result from the use of chitosan. Nevertheless, chitosan use is limited due to its high viscosity, its insolubility in organic solutions, and poor solubility in aqueous solution owing to the pH . Hence, a flourishing interest for lowering the molar masses to obtain chitosan oligomers appeared over the last decade. …”
Section: Introductionmentioning
confidence: 99%
“…A wide range of chitosan exists with various molar masses from 100 000 g/mol up to 500 000 g/mol with acetylation degree between 0 and 30% . Many interesting applications result from the use of chitosan. Nevertheless, chitosan use is limited due to its high viscosity, its insolubility in organic solutions, and poor solubility in aqueous solution owing to the pH . Hence, a flourishing interest for lowering the molar masses to obtain chitosan oligomers appeared over the last decade. …”
Section: Introductionmentioning
confidence: 99%
“…[214][215][216][217] As CS possesses water-binding capacities and reactive properties due to the presence of -NH 2 and -OH groups, it was used as a thickener and binder in textile printing. 218,219 Abdou et al 220 used blends of CS/starch as a thickener in the screen printing of different textile samples (nylon 6, cotton and polyester). They showed that both the color strength and fastness properties of printed fabrics are enhanced.…”
Section: Antiviral Functionalizationmentioning
confidence: 99%
“…214217 As CS possesses water-binding capacities and reactive properties due to the presence of -NH 2 and -OH groups, it was used as a thickener and binder in textile printing. 218,219…”
Section: Chitosan As An Auxiliary Agent In Dyeing and Printing Processesmentioning
confidence: 99%
“…Chitosan has received more attention for its wide range of applications in food science, biology, medicine, cosmetics, environmental protection, which contain potential application value. [4][5][6][7][8][9] Accordingly, new patterns are urgent to equip self-assembled structures of chitosan such as nanowires, hydrogels, membranes, and emulsions which could be applied to various fields. [10,11] As a hydrophilic biopolymer, chitosan is a compound with intramolecular hydrogen bond owing to the presence of plenty of free -NH 2 and -OH in each unit, which allows chitosan to have a strong chelating ability with metal ions.…”
Section: Introductionmentioning
confidence: 99%